Strategi Active Learning dalam Menumbuhkan Minat Membaca Melalui Media Buku Cerita Bergambar Pada Mata Pelajaran Bahasa Indonesia - Lalu Abdul Aziz; Rabiatul Adawiah; Muhamad Sadli (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to describe the implementation of the active learning strategy in fostering students' interest in reading through picture storybooks in the Indonesian language subject for grade II students at SD Negeri 1 Bebidas. The background of this research is the low reading interest among students, which affects their lack of comprehension in reading texts. To overcome this issue, the active learning strategy is applied, emphasizing student engagement and the use of interesting and developmentally appropriate picture storybooks. This study uses a qualitative approach with a descriptive method. The subjects of the study were teachers and students of grade II at SD Negeri 1 Bebidas. Data collection techniques included observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The results of the study show that the application of the active learning strategy through various activities such as paired reading, retelling, and small group discussions using picture storybooks plays an important role in attracting students' attention and helping them understand the content. The conclusion of this study is that the active learning strategy through picture storybooks is effective in fostering reading interest in grade II students in the Indonesian language subject. This strategy is recommended for teachers to apply in the learning process to create an active, enjoyable, and meaningful learning atmosphere.